2021
DOI: 10.3390/bs11030033
|View full text |Cite
|
Sign up to set email alerts
|

Perseverative Cognition and Snack Choice: An Online Pilot Investigation

Abstract: Perseverative cognition (PC), consisting of worry and rumination, has been consistently linked to a variety of poorer health outcomes, namely via the worsening of stress-induced health risk behaviours. However, research into PC and unhealthy food choice, a key health behaviour, still remains relatively unexplored. In the current pilot investigation, 284 participants were recruited to take part in an online food choice paradigm before completing the Perseverative Thinking Questionnaire (PTQ) and the Brief State… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…The current study aimed to build upon a previous pilot investigation [30] in which we aimed to test whether the two facets of perseverative cognition, worry and rumination, would lead to poorer food choice as well as increased (hypothetical) calorie consumption; within two conditions that varied in availability of higher calorie snacks. In line with Hypothesis 1b, the results showed that an increased availability of low-calorie snacks made it twice as likely for an individual to opt for a lower calorie snack relative to the even availability condition.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The current study aimed to build upon a previous pilot investigation [30] in which we aimed to test whether the two facets of perseverative cognition, worry and rumination, would lead to poorer food choice as well as increased (hypothetical) calorie consumption; within two conditions that varied in availability of higher calorie snacks. In line with Hypothesis 1b, the results showed that an increased availability of low-calorie snacks made it twice as likely for an individual to opt for a lower calorie snack relative to the even availability condition.…”
Section: Discussionmentioning
confidence: 99%
“…It could also be argued that the online nature of the study (in which no food was physically consumed by the participants) perhaps limits the conclusions that can be drawn. However, it is noteworthy that as food purchases become ever more accessible online (and or via mobile applications), this does still provide a valid indicator of the desire to order and consume food [30]. Other important considerations of the current food choice paradigm include those of the demand characteristics of the participants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Glucocorticoids, as the effector molecules of the stress response has also been shown to result in an increased tendency to consume high-calorie, palatable foods [51]. In addition, the reduced availability of unhealthy, higher calorie snacks, was found to significantly reduce the likelihood of choosing a higher calorie snack relative to an even availability of high and low calorie snacks [52].…”
Section: Emotions and The Context Of Adolescents' Food Consumptionmentioning
confidence: 99%